2017
DOI: 10.1016/j.ssci.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Training to safety rules use. Some reflections on a case study

Abstract: International audienceThis article proposes to consider training in occupational risk prevention as situated at the crossroads between regulated safety (based on prescribed safety rules and procedures)-and managed safety (based on operators' knowledge and experience). A case study in the field of ready-mixed concrete delivery to worksites is presented. It demonstrates the redefinitions of a safety rule within companies, giving it little operational value for operators, and the resources that they have built wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…§ Topic 3: studies on safety commitment of managers, owners and leaders, which impacts on safety outcomes[20][21][22][23][24][25]. § Topic 4: studies on the effects of safety education and training on workers, which consider behaviour change, situation awareness and other measures for efficacy[26][27][28][29][30][31][32][33][34]. § Topic 5: studies on education programs provided to young or inexperienced workers to increase their level of knowledge and risk awareness[35][36][37][38][39].…”
mentioning
confidence: 99%
“…§ Topic 3: studies on safety commitment of managers, owners and leaders, which impacts on safety outcomes[20][21][22][23][24][25]. § Topic 4: studies on the effects of safety education and training on workers, which consider behaviour change, situation awareness and other measures for efficacy[26][27][28][29][30][31][32][33][34]. § Topic 5: studies on education programs provided to young or inexperienced workers to increase their level of knowledge and risk awareness[35][36][37][38][39].…”
mentioning
confidence: 99%
“…Promotion of individualsʼ education to maintain health is one of the strategic goals of safety and health performance that should be achieved in line with the development and institutionalization of the OHS principles in organizations [64]. Recent studies have shown that OHS training is an important tool in preventing injuries, risks and occupational diseases [65][66][67] because it is a prerequisite for improving OHS [67].…”
Section: Discussionmentioning
confidence: 99%
“…Cet outil et les résultats qu'il produit cherchent alors à proposer des mesures correctives pour rectifier les mauvaises pratiques de l'opérateur générant ces expositions. La conséquence possible de ces usages de la VEM est de reproduire des pratiques de prévention où l'opérateur reste une cible de la prévention à atteindre et à convaincre, et non un acteur à part entière (Clot, 2010 ;Hale & Borys, 2013 ;Mohammed-Brahim & Garrigou, 2009 ;Vidal-Gomel, 2017). L'absence de description des activités (au sens ergonomique du terme) et facteurs influençant l'activité des travailleurs est constatée dans cette littérature.…”
Section: Apport De La Vem à L'hygiène Industrielleunclassified
“…Dans les approches en hygiène industrielle, les activités sont cibles de transformation au détriment des déterminants (techniques, organisationnels et humains) qui les influencent. L'analyse plurifactorielle de la situation d'exposition pouvant porter atteinte à la santé reste partielle par rapport aux pratiques décrites par Daniellou (1992), Garrigou et al (2004), Mohammed-Brahim & Garrigou (2009) et Vidal-Gomel (2017). De plus, la prise en compte des savoirs et représentations des opérateurs exposés n'est pas abordée dans les approches classiques en hygiène industrielle et en prévention, ce qui du point de vue de l'ergonomie reste une voie de développement des recherches et interventions portant sur les expositions professionnelles.…”
Section: Apport De La Vem à L'hygiène Industrielleunclassified